Zur Rolle und Bedeutung der Syntax im Bereich der forensischen Linguistik - Przemysław Staniewski (Linguistische Treffen in Wrocław, 2025)
This review article addresses Isabelle Thormann's book “Tatort Syntax. Authentizitätsfeststellung in der forensischen Linguistik”. The introductory section briefly presents forensic linguistics as a research discipline, considering its narrow and broad definitions as well as its subfields, such as legal linguistics, police language, language in court or in legal proceedings, and other criminal areas where forensic linguistics functions as a “forensic auxiliary science”. In the subsequent and much more extensive section, the book's detailed and comprehensive discussion of the role of syntax in forensic linguistics is addressed. In the first step, the author focuses primarily on theoretical aspects. The following elaborations are, however, very practically oriented and concern two areas: (1) various factors that can be used to identify an idiolect – a central concept of the book – and consequently possibly allow to determine the text authorship. These factors primarily include incorrect use of commas and spelling errors, as well as different syntactic ambiguities. (2) Procedures for coding or marking the mentioned errors. Finally, attention is directed to the last chapter, which has a didactic character and can also be considered a handbook of German syntax (in a simplified form). The article concludes with a general assessment of the book and notes on its potential further applications.